The Ambrysus Stål (Heteroptera: Naucoridae: Cryphocricinae) of Mexico: Revision of the subgenus Syncollus La Rivers - Reynoso-Velasco, Daniel; Sites, Robert W.; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2016)
The subgenus Ambrysus (Syncollus) La Rivers is mostly Neotropical and includes nine described species. Features uniting species in this subgenus are related to the position of the propleura with respect to the prosternum in males and females, as well as characteristics of tergum V and the genitalia of males. Three species of Syncollus are known from Mexico including Ambrysus baeus Polhemus & Polhemus, A. circumcinctus Montandon, and A. pygmaeus La Rivers. The remaining six species in the subgenus are distributed in Central and South America. Herein we review Syncollus and revise the Mexican fauna. More specifically, three new species from Mexico are described: A. chiapanecus n. sp., A. totonacus n. sp., and A. xico n. sp. The subspecies A. circumcinctus caliginosus Usinger, A. c. concavus La Rivers, and A. c. extremus La Rivers are proposed as junior synonyms of A. c. circumcinctus Montandon. Ambrysus partridgei De Carlo is transferred from Syncollus to the subgenus Ambrysus.